Imperfect Information and Saving in a Small Open Economy - Roitman, Agustin (IMF Working Papers; Working Paper ;, 2011)
Emerging markets are more volatile and face different types of shocks, in size and nature, compared to their developed counterparts. Accurate identification of the stochastic properties of shocks is difficult. We show evidence suggesting that uncertainty about the underlying stochastic process is present in commodity prices. In addition, we build a dynamic stochastic general equilibrium model with informational frictions, which explicitly considers uncertainty about the nature of shocks. When formulating expectations, the economy assigns some probability to the shocks being temporary even if they are actually permanent. Parameter instability in the stochastic process implies that optimal saving levels (debt holdings) should be higher (lower) compared to a process with fixed parameters. Imperfect information about the nature of shocks matters when commodity GDP shares are high. Thus, economic policies based on misperception of the underlying regime can lead to substantial over/under saving with important associated costs.